Pemberdayaan Terhadap Masyarakat Menuju Desa Green Product, Kesehatan Mental Anak Yang Baik, dan Berpengetahuan Ai - Syahputra, Bintang; Prayuda, Nazwan Putera; Ilham, Muhammad Maulana; Sadewa, Dimas Ibnu; Mubarok, Khoidar; Nurrohman, Ahmad Alfianto; Yofinaldi, Septian; Syaifulloh, Abu Rahman; Anggraini, Dewi; Ardiansa, Bily; Simatupang, Joshe Samuel Maruba (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
The Community Service Program (KKN) carried out by Group 8 aims to empower the people of Bahagia Village towards an environmentally friendly and mentally healthy village. This program involves several main activities such as making hydroponics, catfish hatcheries, making plastic waste banks, socializing the prevention of online game addiction and promiscuity, as well as introducing artificial intelligence (AI) technology. Through this program, it is hoped that the community can obtain alternative sources of income, increase awareness of the importance of environmental management, and understand the impact and benefits of AI technology. The program results show that the activities carried out succeeded in having a positive impact on society both in terms of economics, environment and education.